Purchase of ICT equipment for all activities [Tender documents : T24485190] (MENA Report, 2014)
The subject of the public contract is a contract for the purchase of ict equipment for all activities implemented by consolidating hardware and software including office application virtualization, desktops, servers, infrastructure, increasing safety and security infrastructure tc orp and computerization of processes, data digitization and networking with local ais public administration registers and support for 5 years from...